Interactions between assembly order and temperature can alter both short‐ and long‐term community composition. Issue 16 (28th November 2013) - Clements, Christopher F.; Warren, Philip H.; Collen, Ben; Blackburn, Tim; Worsfold, Nicholas; Petchey, Owen
Abstract: Both the order in which species arrive in a community, and environmental conditions, such as temperature, are known to affect community structure. Little is known, however, about the potential for, and occurrence of, interactions between assembly history and the environment. Of particular, interest may be the interaction between temperature and community assembly dynamics, especially in the light of predicted global climatic change and the fundamental processes that are governed, through metabolic rate, by an individual's environmental temperature. We present, to our knowledge, the first experimental exploration of how the influence of assembly history, temperature, and the interaction between the two alters the structure of communities of competitors, using small‐scale protist microcosm communities where temperature and assembly order were manipulated factorially. In our experiment, the most important driver of long‐term abundance was temperature but long‐lasting assembly order effects influenced the relationship between temperature and abundance. Any advantage of early colonization proved to be short‐lived, and there was rarely any long‐term advantage to colonizing a habitat before other species. The results presented here suggest that environmental conditions shape community composition, but that occasionally temperature could interact with the stochastic nature of community assembly to significantly alter future community composition, especially where temperature change has been large. This could have important implications for the dynamics of both rare and invasive species. Abstract : Both the order in which species arrive in a community, and environmental conditions, such as temperature, are known to affect community structure. We show that short‐term community structure is altered by assembly order effects and long‐term community structure is generally driven by temperature, but in addition that temperature and the order in which species invade a habitat can occasionally interact to profoundly affect community composition.